The necessity of social infrastructure for enhancing educational attainment: evidence from high remittance recipient LMICs - Saydaliev, Hayot Berk; Lee, Chin (Springer Science and Business Media LLC, 2023)
This study investigated the efect of remittance infows on educational attainment with the interaction efect of social infrastructure. The system generalized method of moments (Sys-GMM) technique was applied to analyze data from 69 countries from 1995 to 2019 using a 5-year non-overlapping average. The fndings revealed that: (1) remittances and income have a negative efect on educational attainment in low- and middle-income countries; (2) social infrastructure, government expenditures on education, and institutional quality have a positive efect on educational attainment; (3) remittances alone cannot generate educational attainment; however, when remittances work in tandem with better social infrastructure, it facilitates educational attainment; (4) remittances and social infrastructure have asymmetric efects on educational attainment; and (5) remittances contribute more to females than males in obtaining an education. Thus, the fndings suggest that policymakers should formulate alternative social infrastructure development strategies to render higher returns from remittances.